2004
DOI: 10.1080/13803610512331383509
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing Project-Based Learning Through Online Between-Group Collaboration

Abstract: This research explored how between-group collaboration enhanced the co-construction of knowledge and performance on project-based learning tasks of collaborative learning groups. The findings of 2 case studies, one that focused on between-group mentoring and one that focused on between-group project review, revealed that both strategies were perceived favorably by the students and had a positive impact on the collaborative learning skills, the knowledge revealed through their online dialogue, and the project p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0
4

Year Published

2008
2008
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(42 citation statements)
references
References 36 publications
1
37
0
4
Order By: Relevance
“…Additionally, Tassainari (1996) and Worthy (2000) assert project-based approaches offer learners opportunities to guide, manage and monitor their learning through self-direction and self-regulation. Project-based learning also has the potential to integrate collaboration and cooperation meaningfully (e.g., Helle et al, 2006;Lou & MacGregor, 2004;Mitchell, Foulger, Wetzel, & Rathkey, 2009), where student teams remain intact throughout a project or individuals use peer reviews and more informal social negotiations. Lessons employing project-based learning also use a variety of resources, tools, and scaffolds (Dodge, 1995(Dodge, , 1998Helle et al, 2006;Williams van Rooij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, Tassainari (1996) and Worthy (2000) assert project-based approaches offer learners opportunities to guide, manage and monitor their learning through self-direction and self-regulation. Project-based learning also has the potential to integrate collaboration and cooperation meaningfully (e.g., Helle et al, 2006;Lou & MacGregor, 2004;Mitchell, Foulger, Wetzel, & Rathkey, 2009), where student teams remain intact throughout a project or individuals use peer reviews and more informal social negotiations. Lessons employing project-based learning also use a variety of resources, tools, and scaffolds (Dodge, 1995(Dodge, , 1998Helle et al, 2006;Williams van Rooij, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Johnson, 1985;Lazonder, 2005;Warschauer, 1997), in this paper I am more concerned with how computers mediate the existing shared creative activity of children. In shared online learning environments, computers can be viewed both as a medium through which the collaborative activity takes place and also, perhaps inevitably, as an integral part of that process (Lou & MacGregor, 2004). In the case of the study reported in this paper, and in most creative activities within the music classroom involving computers, the children could have completed the task using other means (albeit not as easily).…”
Section: The Mediating Role Of Technologymentioning
confidence: 94%
“…These CIC interactions expand the learning beyond the limitations of one pair by providing more opportunities for the students to exchange insights, ideas, and strategies, and to learn from each other's strengths and weaknesses (Lou, 2004;Lou & MacGregor, 2004). Furthermore, in the CIC, the context and progress of other working projects provide the students with both motivational support and new insights (Lou, 2004;Lou & MacGregor, 2004). The students provide feedback to each other, and in doing so, they are able to develop critical thinking, self-regulation skills, and metacognition.…”
Section: Supporting Students' Metacognition and Developing Their Envimentioning
confidence: 99%